PERUBAHAN TUTUPAN LAHAN HUTAN DI CAGAR ALAM RAWA DANAU MENGGUNAKAN CITRA LANDSAT DAN SISTEM INFORMASI GEOGRAFI - Munir, Achmad; Atmosoemarto, Mulyadi; Arifien, Yunus (Jurnal Nusa Sylva, 2017)
Rawa Danau Nature Reserve is an area of the old volcanic caldera located in Serang District, Banten Province about 100 km to the west of Jakarta. This area has been identified as a very important natural site on the island of Java. This is based on the fact that the main wetland ecosystem at Rawa Danau is the only remaining freshwater swamp forest ecosystem of peat swamp forests in Java Island. The objective of this study was to identify land cover classes and their changes in Rawa Danau Nature reserve area on 2006, 2011, and 2016, and also calculate degradation rate and reforestation during the time of observation. This study was conducted in April - June 2017. Data sources was generated from landat image ETM+7 coverage year of 2006 and 2011, Image Landsat OLI 8 coverage year 2016 and other supporting digital maps. Supporting tools and instruments used were software, ArcGis 10.1, Erdas 9.1, GPS, Camera and Stationary. The result showed that land cover can be successfully classified both digitally or visually and composed of secondary swamp forest, marsh bushes, fields, settlements, water body and swamp. Highest degradation during 2006-2016 occured on swamp forest that was converted into fields, while highest reforestation happened on fields that became swamp area. Key words: Degradation, Image Landsat, Land Cover Changes, Land Cover